Applying Ostrom's common resource management principles to analyze institutional factors for the failure of the volunteer tourism program for green sea turtles conservation in Lanyu (Orchid Island), Taiwan. Issue 6 (1st November 2020) - Liu, Tzu-Ming
ABSTRACT: Chelonia mydas (green sea turtles, GST) in Lanyu (Orchid Island), Taiwan, affect the behavioral evolution of land-based organisms in Lanyu, and they are also important for the study of evolutionary biology. However, threats to their survival are increasing. To protect GST, conservation organizations have recruited volunteer tourists to assist in the implementation of a GST conservation program. However, the volunteer tourism program for GST conservation did not achieve the expected results, and it even caused serious social conflicts and threatened the survival of GST . In this study, the volunteers and the local Tao people were interviewed to understand the views of both parties, and the interview data were analyzed using Ostrom's common resources management principles. The results showed that wo mechanisms led to the neglect: the appropriate authorities in the Taiwan government did not provide sufficient funds, and the government was unable to integrate and coordinate the conservation activities. The research results suggest that government authorities should provide sufficient funds and communication resources to assist conservation organizations in making use of local ecological conservation mechanisms and that conservation organizations should report the results of volunteer tourism programs to the Tao people and assist in cleaning the beach.